1998
DOI: 10.1677/joe.0.1560023
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin-releasing hormone antagonist arrests premeiotic germ cell proliferation but does not inhibit meiosis in the male monkey: a quantitative analysis using 5-bromodeoxyuridine and dual parameter flow cytometry

Abstract: Meiosis constitutes a crucial phase of spermatogenesis since the recombination of genetic information and production of haploid round spermatids need to be achieved. Although it is well established that gonadotrophic hormones are required for completion of the spermatogenic process, little is known about the dynamic and kinetic aspects of development of spermatocytes into spermatids and its endocrine control in the primate. In this study, S-phase germ cells were labelled using 5-bromodeoxyuridine (BrdU) incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…A similar approach to the study of feedback mechanisms has been reported recently using a 'testicular clamp' in which endogenous gonadotropin secretion was abolished with a GnRH antagonist, and the gonadotropin was replaced by infusion of recombinant human FSH and LH (21). The efficacy of Cetrorelix in suppressing endogenous gonadotropin secretion in cynomolgus monkeys has been established previously (16). The effect of administration of FSH on spermatogenesis in the GnRH antagonist-suppressed nonhuman primate model (22) and the combined treatment using FSH and hCG in the primate have also been reported previously (23).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…A similar approach to the study of feedback mechanisms has been reported recently using a 'testicular clamp' in which endogenous gonadotropin secretion was abolished with a GnRH antagonist, and the gonadotropin was replaced by infusion of recombinant human FSH and LH (21). The efficacy of Cetrorelix in suppressing endogenous gonadotropin secretion in cynomolgus monkeys has been established previously (16). The effect of administration of FSH on spermatogenesis in the GnRH antagonist-suppressed nonhuman primate model (22) and the combined treatment using FSH and hCG in the primate have also been reported previously (23).…”
Section: Discussionmentioning
confidence: 87%
“…The investigators were blinded to the experimental status of the animals. In addition, at study day 0 and on the last study day (day 38) testicular biopsies were performed as previously described (16).…”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Testicular volume was calculated applying a formula for an ellipsoid from length and width measures of the testis using Vernier callipers as described previously (Weinbauer et al 1998, Junaidi et al 2005.…”
Section: Testis Volumementioning
confidence: 99%